2015
DOI: 10.5888/pcd12.140595
|View full text |Cite
|
Sign up to set email alerts
|

Community Member and Stakeholder Perspectives on a Healthy Environment Initiative in North Carolina

Abstract: IntroductionThe North Carolina Community Transformation Grant Project (NC-CTG) aimed to implement policy, system, and environmental strategies to promote healthy eating, active living, tobacco-free living, and clinical and community preventive services to advance health equity and reduce health disparities for the state’s most vulnerable communities. This article presents findings from the Health Equity Collaborative Evaluation and Implementation Project, which assessed community and stakeholder perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…In this study, we drew on the principles and practice of Photovoice. However, because of constraints on time and funding, we did not implement the Photovoice components of collaboratively assigning topics with participants, involving participants in the analysis and/or write-up of the results, nor did we facilitate an action component like some (Carter-Edwards et al, 2015) in which study participants work to address jointly identified issues. Instead, based on previous experiences using in-depth interviews with adolescents in Malawi (Rock et al, 2016), we chose a photo-elicitation approach to involve adolescents in this context in a more engaging way as we describe below.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we drew on the principles and practice of Photovoice. However, because of constraints on time and funding, we did not implement the Photovoice components of collaboratively assigning topics with participants, involving participants in the analysis and/or write-up of the results, nor did we facilitate an action component like some (Carter-Edwards et al, 2015) in which study participants work to address jointly identified issues. Instead, based on previous experiences using in-depth interviews with adolescents in Malawi (Rock et al, 2016), we chose a photo-elicitation approach to involve adolescents in this context in a more engaging way as we describe below.…”
Section: Introductionmentioning
confidence: 99%
“…Third, all 7 PRC’s produced manuscripts for peer-reviewed journals to disseminate findings and lessons learned. Six have been published or are forthcoming ( 19 24 ), and one manuscript was under review at the time of this writing. Finally, 6 PRCs presented evaluation findings at regional or national conferences attended by researchers and practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…The final step of ensuring use and sharing lessons learned is critically needed in this area ( 8 – 10 ). Six PRCs published their evaluation findings, contributing to the evidence base on how to translate PSE strategies into changes in practice ( 19 24 ). Using the CDC framework to guide evaluations of PSE-change initiatives helps evaluators build practice-based evidence for the growing number of PSE-change strategies being used to promote health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, purposive sampling has been successfully employed to recruit physicians and leaders within a community [42]; however, at the population level, it is highly unlikely that a purposive sampling framework would be available and, if not, it would require significant effort to build. Because our research team lacked a database for purposive sampling and recruitment was flagging, the CAB in community 2 recommended that we transition to a convenience sampling method, as in other community engagement studies [43]. Convenience sampling was accomplished by hiring a part-time small business owner who interacted with a diverse cross-section of community members on a daily basis.…”
Section: Discussionmentioning
confidence: 99%